ANALYSIS OF VILLAGE GOVERNANCE IN KEBANGGAN VILLAGESUMBANG DISTRICT, BANYUMAS DISTRICT - Lulu Dwi Setyani; Suryoto Suryoto; Emilius Gudonohadi (DYNAMICS: Journal of Public Administration, 2023)
This research is entitled "Analysis of Village Good Governance in Kebanggan Village, Sumbang District, Banyumas Regency". The purpose of this study is to describe and explain Good Governance in the Village of Kebanggan, Subdistrict of Sumbang. This study used descriptive qualitative method. Determination of informants was determined by purposive sampling method. Data was collected by means of in-depth interviews, observation and documentation. The results of the research used interactive analysis methods and the validity was tested by triangulation of sources. The results of this study indicate that village good governance in Kebanggan Village has not been fully implemented because in the aspect of accountability the realization of the use of the budget is still not optimal, this occurs due to the lack of village government in exploring village potential and the presence of the Covid-19 virus which is another inhibiting factor in equitable development. village. Then in the aspect of openness of budgeting, there is no direct access for the community and there has been no good response from the village government if suggestions and criticisms are submitted directly to individuals. In terms of the rule of law, village regulations that have been made are not studied and socialized to the wider community and there is rarely a general village regulation. Furthermore, in the aspect of participation, it is quite good but in this case attendance is not 100% due to the inaccuracy of the village government in determining the time for deliberation and the lack of absorption of community aspirations due to the lack of forums and the lack of village government in embracing the community so that public trust begins to decline. Meanwhile, in the aspect of transparency, the Kebanggan Village government is quite good because in every activity the village government has installed budget infographic boards, project boards and inscriptions that contain the amount of the budget and the activities carried out. Meanwhile, the implications that can be given are as follows: to explore the wider potential of the village, the village government and the community should work together to develop a village. To deal with public ignorance about village regulations that have been made, the village government should increase work capacity, especially the head of the village in carrying out their duties and functions. Then regarding the decline in public trust, responding to this the village government should be able to maintain commitment to the public by attending every routine RT/RW meeting as well as adding suggestions and criticism boxes to bridge the community who want to express their aspirations individually or directly without going through an institution.